(untitled) (European Journal of Emerging Technology and Discoveries, 2025)
The article presents the results of a study of the possibility of extracting molybdenum from the products of processing refractory black shale ores. The analysis showed high molybdenum concentrations in the recycled ammonia-carbonate solutions at the stripping stage. A liquid extraction method was studied to extract molybdenum from these solutions. A process flow chart for molybdenum extraction is described, including the following main stages: deoxidation of carbonate solutions with sulfuric acid to pH = 1, joint extraction of uranium and molybdenum, selective stripping of molybdenum, neutralization of strips and production of ammonium paramolybdate.